2013
DOI: 10.1164/rccm.201209-1649oc
|View full text |Cite
|
Sign up to set email alerts
|

Critical Illness Myopathy and GLUT4

Abstract: Insufficient GLUT4 translocation results in decreased glucose supply in patients with CIM. Failed AMPK activation is involved. Evoked muscle contraction may prevent muscle-specific AMPK failure, restore GLUT4 disposition, and diminish protein breakdown. Clinical trial registered with http://www.controlled-trials.com (registration number ISRCTN77569430).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 43 publications
7
64
2
2
Order By: Relevance
“…It is easy to understand that the abnormal elevation in HbA1c indicates that the control of blood glucose may be not satisfactory, but studies have confirmed that abnormal elevation in blood glucose is an independent risk factor for the poor prognosis of critically ill patients,[11-13] and strict control of blood glucose is one of the target treatments for these patients. [14-16] Our results also indicated that the 28-day mortality of the patients without a medical history of diabetes (29/151, 19.21%) was significantly higher than that of the patients with definite diabetes (15/211, 7.11%) ( P =0.000). Blood glucose control and complications of diabetes were not as satisfactory as those in patients without diabetes, but the prognosis of critical diseases was relatively satisfactory.…”
Section: Discussionsupporting
confidence: 65%
“…It is easy to understand that the abnormal elevation in HbA1c indicates that the control of blood glucose may be not satisfactory, but studies have confirmed that abnormal elevation in blood glucose is an independent risk factor for the poor prognosis of critically ill patients,[11-13] and strict control of blood glucose is one of the target treatments for these patients. [14-16] Our results also indicated that the 28-day mortality of the patients without a medical history of diabetes (29/151, 19.21%) was significantly higher than that of the patients with definite diabetes (15/211, 7.11%) ( P =0.000). Blood glucose control and complications of diabetes were not as satisfactory as those in patients without diabetes, but the prognosis of critical diseases was relatively satisfactory.…”
Section: Discussionsupporting
confidence: 65%
“…There are still phases in which patients are not available for active physiotherapy, and these intervals often coincide with intervals of severe illness, acute systemic inflammation, or dependency on norepinephrine for hemodynamic stability. These early periods of critical illness and inflammation are particularly significant in the development of muscle wasting and ICU-AW, as we [6, 14] and others [7] could recently show. Evoked muscle training to avoid immobilization due to EMS can be an option [1012, 14], but application is labored, often not feasible [15], and in general EMS therapy for ICU patients remains controversial [38].…”
Section: Discussionsupporting
confidence: 51%
“…These early periods of critical illness and inflammation are particularly significant in the development of muscle wasting and ICU-AW, as we [6, 14] and others [7] could recently show. Evoked muscle training to avoid immobilization due to EMS can be an option [1012, 14], but application is labored, often not feasible [15], and in general EMS therapy for ICU patients remains controversial [38]. Alternatively WBV may be able to close the gap between immobilization and active physiotherapy, hypothesizing that frequently applied early muscle activation evoked by WBV may support patient recovery.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Yet the definition of early mobilization is rather vague, as it encompasses a wide range of techniques practiced on different ICU populations [2, 3]. Nevertheless, early mobility interventions in critically ill patients prove to be feasible and safe in preventing bed-rest-associated morbidity [46], while improving patients’ physical function [7], psychological condition [8], and quality of life [9]. Mobilizing patients at an early time point has been associated with reduced health care costs [10], as such intervention decreases invasive mechanical ventilation (MV) duration, delirium [7, 11], and hospital length of stay [12].…”
Section: Introductionmentioning
confidence: 99%